Malacological survey of Biomphalaria snails in municipalities along the Estrada Real in the southeast of the State of Minas Gerais, Brazil Pesquisa malacológica de Biomphalaria em municípios da Estrada Real, situados no sudeste do Estado de Minas Gerais - Sandra Helena Cerrato Tibiriçá; Adalberto Mitterofhe; Milton Ferreira de Castro; Adilson da Costa Lima; Murilo Gonçalves; Izabella de Oliveira Pinheiro; Corina da Costa Freitas; Ricardo José Paula de Souza e Guimarães; Omar dos Santos Carvalho; Elaine Soares Coimbra (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: The increasing practice of ecotourism and rural tourism in the State of Minas Gerais, Brazil, highlights the importance of studies concerning the occurrence of potential intermediate hosts of Schistosoma mansoni. This study aimed to identify species of Biomphalaria snails in municipalities along the Estrada Real, an important Brazilian tourism project. METHODS: The specimens were collected in different water collections of 36 municipalities along the Estrada Real in the southeast of the State of Minas Gerais. Biomphalaria species were characterized using both morphological and molecular approaches. The research was conducted between August 2005 and September 2009 and all the sites visited were georeferenced using GPS. RESULTS: Six Biomphalaria species were found in 30 of the 36 municipalities studied: glabrata, tenagophila, straminea, peregrina, occidentalis and schrammi. The first three species of Biomphalaria, recognized as intermediate hosts of S. mansoni, were present in 33.3%, 47.2% and 8.3% of the municipalities studied, respectively. The mollusks were found in different types of water collections and no infection by S. mansoni was detected. The highest occurrence of Biomphalaria concentration was verified in the area covered by the Caminho Novo route (Diamantina/MG to Rio de Janeiro/RJ). CONCLUSIONS: Considering the occurrence of schistosomiasis in the State of Minas Gerais and the socioeconomic repercussions involved in the Estrada Real Project, this work focuses on the vulnerability of water collections due to the presence of Biomphalaria mollusks and emphasizes the need for epidemiological surveillance and sanitary and educational measures integrated with the local community and tourism sectors. INTRODUÇÃO: O aumento das práticas de ecoturismo e turismo rural, em Minas Gerais, Brasil, evidencia a importância de se realizarem estudos sobre a ocorrência de hospedeiros intermediários do Schistosoma mansoni, no estado. O presente trabalho objetivou a busca e identificação das espécies de caramujos Biomphalaria encontrados em municípios mineiros pertencentes à Estrada Real, um importante projeto de turismo brasileiro. MÉTODOS: Os moluscos foram coletados em 36 municípios da Estrada Real, no sudeste de Minas Gerais. A pesquisa foi realizada de agosto de 2005 a setembro de 2009 e todos os locais visitados foram georreferenciados com o uso de GPS. RESULTADOS: Dos 36 municípios estudados, 30 apresentaram a ocorrência de pelo menos uma entre as seis espécies de Biomphalaria: glabrata, tenagophila, straminea, peregrina, occidentalis e schrammi. As três primeiras espécies citadas, reconhecidas como hospedeiras intermediárias do S. mansoni, estavam presentes em 33,3%, 47,2% e 8,3% dos municípios estudados, respectivamente. Os moluscos foram encontrados em diferentes tipos de coleções hídricas e em nenhum deles foi detectada infecção pelo S. mansoni. Houve maior ocorrência de Biomphalaria na área referente ao Caminho Novo (Diamantina/MG ao Rio de Janeiro/RJ). CONCLUSÕES: Considerando-se a ocorrência da esquistossomose, no Estado de Minas Gerais, e as repercussões socioeconômicas que envolvem o projeto Estrada Real, este trabalho aponta para a vulnerabilidade das coleções hídricas devido à presença de moluscos Biomphalaria e enfatiza a necessidade de vigilância epidemiológica e medidas educativas e sanitárias integradas com a comunidade local e setores de turismo.